PENGARUH KONSERVATISMA AKUNTANSI TERHADAP ASIMETRI INFORMASI - , Sri Ruwanti, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The study aims to examine the effect of accounting conservatism on information asymmetry. Sampling using a purposive sampling method produces a sample of 85 companies, of the years from 2007 to 2009. Data obtained from various sources that the Indonesian Stock Exchange website, Data Center Economics and Business Faculty of Economics and Business UGM and from OSIRIS. Data were tested using linear regression. The research was motivated by research Lafond and Watts (2008) who found results that information asymmetry is positively related to conservatism. The results of this study showed no effect of accounting conservatism on information asymmetry. This means that the company's actions to be conservative or not, does not affect the behavior of investors on its investment. In addition, possibly because investors consider the other variables for the actions of its investment.